MANAJEMEN KELAS UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI MTsN 4 TULUNGAGUNG - Yusufu Nicolas Arswendo; Luluk Indarti (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
The problem discussed in this paper is how to improve the quality of learning in schools, therefore good classroom management is needed. Class management from planning, implementation, and evaluation is needed to create a good learning atmosphere. This research was conducted with the aim of knowing the planning, implementation, and evaluation of classroom management at MTsN 4 Tulungagung. This study uses a qualitative approach with the type of case study research in exploring the learning process. The in-depth interview technique is a step in collecting data with principals, teachers, and students at MTsN 4 Tulungagung.. The results of this study indicate that (1) Classroom Management Planning to improve the quality of learning at MTsN 4 Tulungagung is carried out by preparing class arrangement scenarios, selecting methods and media in learning devices, (2) Class Management Implementation to improve the quality of learning at MTsN 4 Tulungagung is carried out by creating an appropriate learning climate, setting up classrooms which consist of setting up benches and providing classroom facilities, and providing a pattern of teaching and learning interactions between teachers and students, and (3) Evaluation of Class Management to improve the quality of learning at MTsN 4 Tulungagung is carried out by evaluating the facilities provided. exist in schools and processes by the principal, and Evaluation of Learning in the classroom by teachers with skills, knowledge through daily and semester assessments shown by students.